OPTIMASI FORMULASI SABUN MANDI CAIR EKSTRAK ETANOL RIMPANG JAHE MERAH (Zingiber officinale Rosc. var rubrum) DENGAN METODE SIMPLEX LATTICE DESIGN - Randi Mulyana Putra; Andhi Fahrurroji; Bambang Wijianto (Jurnal Teknosains, 2016)
Prevention of diseases caused by bacteria can be carried out with the use of antibacterial soap. The use of antibacterial soaps derived from natural one is to plant a red ginger (Zingiber officinale Rosc. var rubrum) which proved to have antibacterial activity. Therefore, preparations to make it more acceptable liquid soap containing antibacterial compounds 6-shogaol, gingerol, and zingiberen from red ginger plant. Simplex Lattice Design is a method which to find a good formula of dosage from. The study aims to determine the optimum formulation liquid soap ethanolic extract of red ginger rhizome using the method of Simplex Lattice Design. Simplex Lattice Design Methods used to optimize the formulation of liquid soap with five formulas with variations in the amount of olive oil and potassium hydroxide (KOH), FI (0%:100%), FII (25%:75%), FIII (50%:50%), FIV (75%:25%), FV (100%:0%). Evaluation of liquid soap ethanol extract of red ginger rhizome (Zingiber officinale Rosc. var rubrum) include an examination viscosity, pH, and free alkali. Physical stability was analized to find higher total response value (R total) as parameter of the optimum formula by Simplex Lattice Design Methods with Design Expert software  version 8.0.7.1. Optimum formula liquid soap ethanolic extract of red ginger rhizome with the proportion of variation base olive oil 98,1%(27,167 g) and potassium hydroxide (KOH) 1,9%(3,99 g). Data obtained physical characteristics test compared with prediction value using Design Expert software version 8.0.7.1. The result showed that physical properties of liquid soap formula optimum didn’t different significantly for easy response.